Cell volume restriction by mercury chloride reduces M1-like inflammatory response of bone marrow-derived macrophages - Chuang, Yen-Chieh; Wu, Shu-Yu; Huang, Yu-Chuan; Peng, Chung-Kan; Tang, Shih-En; Huang, Kun-Lun (Frontiers in Pharmacology, 2022)
Dysregulation of macrophages in the pro-inflammatory (M1) and anti-inflammatory (M2) sub-phenotypes is a crucial element in several inflammation-related diseases and injuries. We investigated the role of aquaporin (AQP) in macrophage polarization using AQP pan-inhibitor mercury chloride (HgCl2). Lipopolysaccharides (LPSs) induced the expression of AQP-1 and AQP-9 which increased the cell size of bone marrow-derived macrophages. The inhibition of AQPs by HgCl2 abolished cell size changes and significantly suppressed M1 polarization. HgCl2 significantly reduced the activation of the nuclear factor kappa B (NF-κB) and p38 mitogen-activated protein kinase (MAPK) pathways and inhibited the production of IL-1β. HgCl2 attenuated LPS-induced activation of mitochondria and reactive oxygen species production and autophagy was promoted by HgCl2. The increase in the light chain three II/light chain three I ratio and the reduction in PTEN-induced kinase one expression suggests the recycling of damaged mitochondria and the restoration of mitochondrial activity by HgCl2. In summary, the present study demonstrates a possible mechanism of the AQP inhibitor HgCl2 in macrophage M1 polarization through the restriction of cell volume change, suppression of the p38 MAPK/NFκB pathway, and promotion of autophagy.